Konsep Kepemimpinan Menurut Al-Ghazālī - Masykur Hakim (ILMU USHULUDDIN, 2018)
According to al-Ghazālī, the presence of the leader is very important in a country or in a community for keeping peace, comfort and orderly in the society. It is a religious obligation for Muslims or their representative to choose the capable leader in order to gain the common interests of the people and the instructions of religion coukd running well suited to their expectations. Even he allowed the Muslim cleric to participate in the politics practically or become members of the House in order the all programmes of the government are implemented smoothly. If the Muslim intellectuals of the country could not criticize the indisciplines of the government to Islamic laws or its disobidiences to the regulations preferablely they take the opposition side and become the real opposant. Still more of his Islamic political thoughts are interested to be elaborated deeper in this paper.